The influence of structured supportive education on knowledge and attitude of parents with children suffering from upper respiratory tract infection to the envrionmental health - Dias Afrida Leolita; Atika Dhiah Anggraeni (UM Purwokerto Press, 2020)
The upper respiratory tract infection (URTI) is possibly caused by the home environmental factors, individual factors and attitude factors. URTI is one major health problem occurring in, particularly children under 5 years old. The structured supportive education is an interactive process to encourage learning efforts to add new knowledge, attitudes, and skills through both practical strengthening and exceptional experiences. The purpose of this research is to figure out the effect of structured supportive education on knowledge and attitudes of mothers with children experiencing theupper respiratory tract infection (URTI). This research employed as qualitative method with a quasi-experimental design and pretest-posttest one group design approach. The research result indicated that structured supportive education affected knowledge and attitude with thep-valueof 0.046. It is expected that the result of this research is possibly used as one treatment intervention media to improve the knowledge and attitude of parents with children experiencing theupper respiratory tract infection (URTI). Besed on the results of research on Structured Supportive Education, it is significantly more influential in improving the knowledge and attitudes of parents.